PENDAMPINGAN BAGI FASILITATOR PENDERITA HIPERTENSI DI KABUPATEN KUBU RAYA MELALUI DISEMINASI DIET DASH - Oke Anandika Lestari; Yohana Sutiknyawati Kusuma Dewi; Nurmainah Nurmainah (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
This assistance activity for hypertension facilitator in Kabupaten Kubu Raya through DASH Diet (Dietary Approaches to Stop Hypertension) dissemination is Community Partnership Program (PKM) with it purpose are to increase knowledge and skill of food preparation and food making with DASH Diet approach. The background of this activity is the high number of hypertension patients in Kabupaten Kubu Raya. In DASH Diet approach, consumption of fruit and vegetable or high potassium intake is highly suggested. Partner in this Partnership activity are Community Health Centre (Puskesmas) of Sungai Raya Dalam and PKK (Family Welfare Community) of Kabupaten Kubu Raya. Participant are cadre anddelegation from Integrated Service Community (Posyandu) in Kubu Raya. Method used are socialization, training and assistance, and evaluation. DASH Diet is made enriched food with fruit and vegetables, which are cookies with pineapple and low gluten composite noodleenriched with carrot. Participants experienced a very useful assistance supported by comprehension score 62% for understand, and 32% very understand. Applied processed food has preferable score 74% for fruit cookies, and 63% score for low gluten noodle. Participant are expected to distribute the knowledge and applied it at least in family level. Healthy food application in the future will be developed, not only for it health benefit but also preferable taste.